Hydrochemistry of water samples during METEOR cruise M138 - Hermann W Bange; Lukas Eck; Sinikka T Lennartz; Martina Lohmann; Kerstin Nachtigall (PANGAEA, 2021)
R/V Meteor (cruise # M138) departed from Callao (Peru) on 01 June 2017 and arrived in Bahia Las Minas (Panama) on 03 July 2017. The main working area off Peru covered both the coastal upwelling and OMZ region between 10°S and 16°S. An equatorial transect from 4°S 86°W to 2°N 86°W was added as an extension of the original cruise track. M138 combined measurements of marine biogeochemistry, microbiology, physical oceanography and air chemistry. The bottle file contains data from the discrete samples taken on CTD casts, including data from the S/T/P/O sensor (See cruise report: Bange et al., Meteor-Berichte, 138. Gutachterpanel Forschungsschiffe, Bonn, Germany, 69 pp.; doi: 10.2312/cr_m138).